Análise experimental do desempenho de tensores de fôrmas para reservatórios de concreto - Gomes, Demóstenes Coutinho (2020)
The percolation of water in concrete reservoirs is the main causative agent of pathologies and the main responsible for reducing the useful life of these structures. This work is dedicated to studying the pathologies and the effects of water percolation in distribution reservoirs molded in loco, especially in the regions where the formwork tensioners are installed, which is a critical point of water infiltration. The study proposes experimental models that describe the behavior of water penetration depths in different tensioners, such as with flat bar and neoprene and with threaded bar and split sleeve. The tests performed were planned using the central rotational composite design. The variables analyzed to quantify water penetration were pressure and time, validated with an error of less than 5% in relation to the values predicted in the model and observed in the experiment. The results show that the flat bar tensioner had the worst performance, as it increased the water infiltration in the structure by 146.62% and the threaded bar tensioner caused the water percolation increase by 104.01%, in relation to the most critical experimental situation. The study presents data that show the infiltration of water in relation to pressure, time and type of tensor. The analysis of this data can be used to improve the performance of these parts.